Avaliação clínica da aplicação local de gel de lorexidina com microbrush no tratamento de bolsas periodontais residuais - Gonçalves, Elonice Melo de Sousa (2015)
Topical application of antibiotics and antibacterials in the treatment of nonresponders located sites can overcome the shortcomings of scaling and root planning (SRP) therapy. The purpose of this split-mouth study, was to evaluate the clinical and microbiological effects, in short time, the chlorhexidine gel 0.2% in control of subgingival plaque in 20 patients with chronic periodontitis previously treated with SRP. All 4 patients had residual periodontal pockets with probing depth (PD) ≥ 5 mm and bleeding on probing and were randomly divided into groups: negative control (C), positive control (SRP), SRP + chlorhexidine (SRPC) and chlorhexidine test (CLX). The visible plaque index (PI), gingival bleeding index (GI), probing depth (PD), bleeding on probing (BOP), gingival recession (GR) and clinical attachment level (CAL) clinical parameters were evaluated by a calibrated and trained researcher who performed the periodontal monitoring at baseline, 30, 90 and 180 days after treatments. The presence of periodontal pathogens Aggregatibacter actinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg), Prevotella intermedia (Pi) and Tannerella forsythia (Tf) was assessed by means of PRC. Data were statistically analyzed by softawe Boestat 5.0. The level of significance was 5%. Six months after treatment, PI and GI reduced for all groups (p <0.05); SRP, SRPC and CLX groups showed a reduction in BOP and also significantly reduced the BOP when compared to C (p <0.05). The PD was reduced to SRP, SRPC and CLX (p <0.05) groups; CAL increased for SRPC and SRP (p <0.05) and GR increased to SRP C and CLX (p <0.05). The SRPC and CLX groups showed significant reduction in the percentage of sites with presence of some bacteria (p <0.05). The RARC group showed the lowest prevalence of bacteria compared differences between groups. The use of chlorhexidine gel with microbrush, with or without the SRP, as an alternative for the treatment of residual periodontal pockets promotes microbiological benefits without providing significant clinical changes.